(untitled) (Bangladesh Agronomy Journal, 2015)
A field experiment was carried out at Agronomy Farm of Patuakhali Science and Technology University, Dumki, Patuakhali, from December 2011 to March 2012, to study the effects of nutrient foliar spray on soybean growth, yield and protein content. Soybean variety Shohag was used as the test crop. N, NPK, NPKS and NPKMg were sprayed and applied in the soil at vegetative and pod filling stages. Soil fertilizations were done as recommended dose, and no soil and foliar fertilization were considered as control. Plants were sprayed at the rate of 100 mg/L of water corresponding to each nutrient. The experimental design was a split plot with three replications. Result indicated that nutrient foliar spray, either singly or in combination, enhanced the growth and yield of the soybean as well as protein content in soybean seed, at the two growth stages compared to soil fertilization. However, spraying nutrients during pod filling stage was better than vegetative spraying stage in all characters studied. The highest amount of protein content in soybean seed and grain yield were obtained by spraying NPKMg. Bangladesh Agron. J. 2014, 17(1): 67-72